Ambiance Measurement - Varun, Veera; 59, Oviya (International Journal of Students’ Research in Technology & Management, 2015)
Air pollution is posing a major threat to the environment. The amount of toxic gases present in air is increasing above the permissible level. This is mainly due to emissions from various industries and automobiles. So monitoring the level of various pollutants in air is necessary to maintain air pollution within the limit. The present method consists of separate equipments for monitoring different types of gases in air. This paper says about implementation with novel sensor system for the measurement of indoor air quality for carbon monoxide, carbon dioxide, temperature and relative humidity in a single integrated circuit. It consists of four sensors for measuring carbon monoxide, carbon dioxide, temperature and relative humidity. The outputs from four sensors are given to PIC microcontroller. It performs analog to digital conversion and displays the level of values in Liquid Crystal Display. Thus the level of toxic gases, temperature and relative humidity is measured with minimum deviation using simple circuits and low cost sensors. The implementation of this system in hazardous gas emitting area is a major scope in future. Further studies can be carried over and better efficiency and accuracy can be produced.